Cooking the southern African way / Kari A Cornell; Peter Thomas - Cornell, Kari A.
An introduction to southern African cooking, featuring traditional recipes for rusks, salads, stews, desserts, holiday food, and more. Also includes information on the history, geography, customs, and people of this region.